Electrode plate and lithium ion battery

By adopting a combined structure of functional coating and active material coating on the lithium-ion battery electrode, the problem of lithium-ion battery electrode edge analysis is solved, the charging rate performance is improved and the battery energy density is maintained.

CN222546368UActive Publication Date: 2025-02-28HUIZHOU LIWINON NEW ENERGY TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202420832176.2
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2024-04-19
Publication Date
2025-02-28
Estimated Expiration
2034-04-19

AI Technical Summary

Technical Problem

The lithium-ion battery edge lithium-ion battery electrode plate problem leads to failure of battery cell performance and safety risks. It is difficult for the existing technology to effectively control the lithium-ion discharge speed, affecting the charging rate performance.

Method used

The combined structure of functional coating and active material coating is adopted. The functional coating is coated on the edges on both sides of the current collector. The active material coating covers the functional coating. By adjusting the thickness ratio of the functional coating to the current collector and the coating parameters, lithium ions are transported within a reasonable range.

Benefits of technology

Effectively control the lithium ion discharge rate, reduce edge lithium extraction, improve the charging window rate performance, and maintain battery energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure HDA0004802460840000011
    Figure HDA0004802460840000011
  • Figure HDA0004802460840000012
    Figure HDA0004802460840000012
Patent Text Reader

Abstract

The utility model discloses an electrode plate and a lithium ion battery. The electrode plate comprises a current collector, a positive electrode and a negative electrode, the edges of the two sides of the current collector are coated with the functional coatings; the active material coating is coated on at least one surface of the current collector and covers the functional coating; the ratio of the thickness of the functional coating to the thickness of the current collector is 0.2-1, and the functional coating is used for weakening lithium ion transmission. According to the invention, the balance between the conductivity of the coating and the lithium removal capacity of the active substance is maintained by adjusting the parameters of the coating, that is, the lithium ion de-intercalation speed is controlled by optimizing the structure and parameters of the pole piece coating, so that the capacity of improving the charging rate of the battery cell is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of secondary batteries, and in particular to an electrode sheet and a lithium-ion battery. Background Art

[0002] At present, lithium-ion batteries are widely used in various digital products and power battery fields due to their high energy density. With the growing demand for fast charging technology in digital products, the charging window of batteries faces unprecedented challenges. In particular, there are some technical problems that have not been fully resolved in the design and function of battery electrodes.

[0003] Lithium-ion batteries have significant edge effects and interface problems at their ends, especially near the edges of the battery. Due to differences in the structure and material properties of the edge of the battery and the main body of the battery, the rate of lithium ion insertion and extraction at the edge of the battery is inconsistent with that of the main body of the battery. This inconsistency may cause excessive precipitation of lithium ions at the edge, which in turn causes lithium deposition at the edge of the battery pole piece, causing the end of the battery to be too thick, resulting in performance failure and safety risks.

[0004] The main solution at present includes overall thinning of the battery pole piece to increase the reaction window at the edge. However, this method may reduce the overall energy density of the battery. Another solution is to apply a coating on the edge to reduce the rate of lithium ion detachment from the positive electrode, thereby improving the lithium deposition problem at the edge. However, this method has a major technical difficulty: the rate of lithium ion detachment in the edge area of ​​the positive electrode needs to be controlled within a reasonable range. Otherwise, when the rate of lithium ion detachment from the edge coating is too slow, a large polarization will still cause lithium deposition at the edge and affect the charging window rate performance.

[0005] In view of these problems, there is an urgent need to develop an innovative technical solution that can effectively control the problem of lithium plating at the edge of lithium-ion battery electrodes and improve the battery's charge rate performance. Utility Model Content

[0006] The purpose of the utility model is to provide an electrode sheet to solve the problem of lithium deposition at the edge of the electrode sheet of the existing lithium-ion battery and improve the charging rate performance of the battery in view of the shortcomings of the prior art.

[0007] In order to achieve the above purpose, the utility model adopts the following technical solutions:

[0008] An electrode sheet, comprising:

[0009] current collector;

[0010] A functional coating, coated on the edges of both sides of the current collector;

[0011] An active material coating, coated on at least one surface of the current collector and covering the functional coating;

[0012] The thickness ratio of the functional coating layer to the current collector is 0.2 to 1, wherein the preferred value is 0.4 to 0.8. The resistance of the functional coating layer is greater than the resistance of the active material coating layer.

[0013] The parameters of the functional coating and the active material coating satisfy the relationship: L·R / S>0.03; wherein L is the width of the functional coating, R is the resistance of the functional coating, and S is the specific surface area of ​​the active substance of the active material coating.

[0014] Controlling the thickness of the functional coating and the current collector to meet a certain ratio can improve the balance between the conduction electrons and the isolation electrons of the current collector, so that the lithium ion transmission in the edge area is within a reasonable range, thereby improving the edge lithium plating and further improving the charging window rate performance.

[0015] Furthermore, the lithium ion extraction rate in the cathode electrode can be controlled by controlling the relationship between the three parameters L, R and S. When the parameters satisfy L*R / S>0.03, the lithium deposition at the edge can be further improved, and the charging window of the lithium-ion battery can be improved. The best improvement can be 0.5C, and the surface density can be increased by at least 10mg, thereby controlling the lithium ion extraction speed and achieving the control of the battery cell charging rate.

[0016] Preferably, the width L of the functional coating is 0.002-0.01 m, wherein the preferred value is 0.004-0.006 m.

[0017] Preferably, the resistance R of the functional coating is 0.1 to 4Ω, wherein the preferred value is 0.5 to 2Ω.

[0018] Preferably, the thickness of the functional coating is 1 to 10 um, with a preferred value of 3 to 6 um, and the thickness of the current collector is 4 to 8 um.

[0019] Preferably, the specific surface area S of the active material in the active material coating is 0.1 to 0.2 m 2 / g, wherein the preferred value is 0.13 to 0.17 m 2 / g.

[0020] Preferably, the active material coating has a resistance of 0.1 to 2Ω, with a preferred value being 0.5 to 1Ω.

[0021] Preferably, the active material coating comprises: a first active material coating coated on at least one surface of the current collector; and a second active material coating connected to both side edges of the first active material coating and covering the functional coating.

[0022] Preferably, the thickness ratio of the second active material coating to the functional coating is 3-10, wherein the preferred value is 6-9.

[0023] Preferably, the thickness of the first active material coating is 30-50 um, wherein the preferred value is 35-45 um.

[0024] Preferably, the thickness of the second active material coating is 20-49 um, with a preferred value being 25-35 um.

[0025] Preferably, the active material coating comprises an active substance, a binder and a conductive agent, and the functional coating comprises a binder and a conductive agent.

[0026] Preferably, the active material is one or more of lithium cobalt oxide, lithium manganese oxide, ternary material, and lithium iron phosphate.

[0027] Preferably, the binder is one or more of polyvinylidene fluoride, polymethyl methacrylate, polytetrafluoroethylene, and polyacrylic acid.

[0028] Preferably, the conductive agent is composed of one or more of carbon black, conductive carbon, acetylene black, carbon nanotubes, carbon nanofibers, graphene and Ketjen black.

[0029] Preferably, the binder accounts for 80-90% of the functional coating, and the conductive agent accounts for 10-20%.

[0030] In addition, the present application also provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet and a separator separated between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet and the negative electrode sheet are the electrode sheets described above.

[0031] Compared with the prior art, the beneficial effects of the utility model are as follows: the electrode sheet provided by the present application is prepared by coating a functional coating on the edges of both sides of the current collector, and coating an active material coating on the surface of the current collector and covering the functional coating; by adjusting the coating parameters so that the ratio of the functional coating thickness to the current collector thickness is 0.2 to 1, a balance is maintained between the conductivity of the coating and the lithium removal ability of the active material, so that the lithium ion transmission in the edge area is within a reasonable range, and the rate performance of the charging window is maintained while avoiding lithium deposition at the edge.

[0032] Therefore, the present application optimizes the electrode coating structure and parameters to control the overall lithium ion insertion and extraction speed, thereby achieving the ability to improve the charging rate of the battery cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a schematic diagram of the longitudinal section structure of the electrode sheet of Example 1 of the utility model.

[0034] Figure 2 This is a schematic diagram of the longitudinal section structure of the active material coating of the electrode sheet of Example 1 of the utility model.

[0035] Among them, 1 is current collector; 2 is functional coating; 3 is active material coating; 31 is first active material coating; 32 is second active material coating. DETAILED DESCRIPTION

[0036] In order to make the technical solution and advantages of the utility model clearer, the utility model and its beneficial effects will be further described in detail below in combination with specific implementation methods and drawings of the specification, but the implementation methods of the utility model are not limited thereto.

[0037] like Figure 1 As shown, the present application provides an electrode sheet, which includes a current collector 1; a functional coating 2 coated on the edges of both sides of the current collector 1; an active material coating 3 coated on at least one surface of the current collector 1 and covering the functional coating 2; the thickness ratio of the functional coating 2 to the current collector 1 is 0.2 to 1, and the resistance of the functional coating 2 is greater than the resistance of the active material coating 3.

[0038] The parameters of the functional coating 2 and the active material coating 3 satisfy the relationship: L·R / S>0.03;

[0039] Wherein, L is the width of the functional coating 2 , R is the resistance of the functional coating 2 , and S is the specific surface area of ​​the active material of the active material coating 3 .

[0040] By adjusting the coating parameters to meet the ratio of the functional coating thickness to the current collector thickness of 0.2 to 1, and L·R / S>0.03, that is, the width L of the functional coating, the resistance R of the functional coating and the specific surface area S of the active material coating, controlling the three parameters can maintain the balance between the conductivity of the coating and the separation ability of the active material. When lithium ions are released quickly and the specific surface area of ​​the active material is large, by controlling the resistance of the coating, the separation speed of the active material is reduced, and the speed at which the negative electrode receives lithium ions is reduced, so that it can withstand a higher charge rate.

[0041] In one embodiment of the present application, the thickness ratio of the functional coating 2 to the current collector 1 is 0.2-1, for example, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, or 1.0.

[0042] In one embodiment of the present application, the width L of the functional coating 2 is 0.002-0.01 m, for example, 0.002 m, 0.003 m, 0.004 m, 0.005 m, 0.006 m, 0.007 m, 0.008 m, 0.009 m, 0.01 m. If the width is too large, the energy density will be lost and the amount of lithium ion transfer cannot be adjusted. If the width is too small, there will be no effect.

[0043] In one embodiment of the present application, the resistance R of the functional coating 2 is 0.1-4Ω, for example, 0.1Ω, 0.2Ω, 0.4Ω, 0.6Ω, 0.8Ω, 1.0Ω, 1.2Ω, 1.4Ω, 1.6Ω, 1.8Ω, 2.0Ω, 2.2Ω, 2.4Ω, 2.6Ω, 2.8Ω, 3.0Ω, 3.2Ω, 3.4Ω, 3.6Ω, 3.8Ω, 4.0Ω. Too large a resistance will affect the impedance of the battery cell and damage the battery cell performance, while too small a resistance will have no effect.

[0044] In one embodiment of the present application, the thickness of the functional coating 2 is 1 to 10 um, for example, it can be 1 um, 2 um, 3 um, 4 um, 5 um, 6 um, 7 um, 8 um, 9 um, 10 um, and the thickness of the current collector is 4 to 8 um, for example, it can be 4 um, 5 um, 6 um, 7 um, 8 um.

[0045] In one embodiment of the present application, the specific surface area S of the active material in the active material coating 3 is 0.1 to 0.2 m 2 / g, for example, it can be 0.1m 2 / g, 0.12m 2 / g, 0.13m 2 / g, 0.14m 2 / g, 0.15m 2 / g, 0.16m 2 / g, 0.17m 2 / g, 0.18m 2 / g, 0.2m 2 / g.

[0046] In one embodiment of the present application, the resistance of the active material coating 3 is 0.1-2Ω, for example, 0.1Ω, 0.3Ω, 0.5Ω, 0.7Ω, 0.9Ω, 1.1Ω, 1.3Ω, 1.5Ω, 1.7Ω, 1.9Ω, or 2Ω.

[0047] like Figure 2 As shown, in one embodiment according to the present application, the active material coating 3 includes: a first active material coating 31, coated on at least one surface of the current collector;

[0048] The second active material coating 32 is connected to both side edges of the first active material coating 31 and covers the functional coating 2 .

[0049] In one embodiment of the present application, the thickness ratio of the second active material coating 32 to the functional coating 2 is 3-10, for example, 3, 4, 5, 6, 7, 8, 9, or 10.

[0050] In one embodiment of the present application, the thickness of the first active material coating 31 is 30-50 um, for example, 30 um, 35 um, 40 um, 45 um, or 50 um.

[0051] In one embodiment of the present application, the thickness of the second active material coating 32 is 20-49 um, for example, 25 um, 30 um, 35 um, 40 um, 45 um, 49 um. In one embodiment of the present application, the active material coating 3 includes an active substance, a binder and a conductive agent, and the functional coating includes a binder and a conductive agent.

[0052] In one embodiment of the present application, the active material is one or more of lithium cobalt oxide, lithium manganese oxide, ternary material, and lithium iron phosphate.

[0053] In one embodiment of the present application, the binder is one or more of polyvinylidene fluoride, polymethyl methacrylate, polytetrafluoroethylene, and polyacrylic acid.

[0054] In one embodiment of the present application, the conductive agent is composed of one or more of carbon black, conductive carbon, acetylene black, carbon nanotubes, carbon nanofibers, graphene and Ketjen black.

[0055] In one embodiment of the present application, the binder in the functional coating 2 accounts for 80-90%, and the conductive agent accounts for 10-20%.

[0056] According to the second aspect of the present application, the present application provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet and a separator separated between the positive electrode sheet and the negative electrode sheet, wherein the negative electrode sheet and / or the positive electrode sheet is the above-mentioned electrode sheet.

[0057] Example 1

[0058] positive electrode:

[0059] like Figures 1-2As shown, the positive electrode sheet provided in this embodiment includes a positive electrode collector 1, a functional coating 2 coated on the edges on both sides of the positive electrode collector 1; and an active material coating 3 coated on the surface of the positive electrode collector 1 and covering the functional coating 2; wherein the active material coating 3 includes a first active material coating 31 coated on the surface of the current collector 1, and a second active material coating 32 connected to the edges on both sides of the first active material coating 31 and covering the functional coating 2.

[0060] The parameters of the functional coating 2 and the active material coating 3 satisfy the relationship: L·R / S>0.03; specifically, the width L of the functional coating 2 is 0.005m, and the resistance R is 1Ω; the specific surface area S of the positive active material of the active material coating 3 is 0.15m 2 / g.

[0061] The thickness of the current collector layer 1 is 5 um, and the thickness of the functional coating 2 is 2 um.

[0062] The functional coating 2 includes a binder (PVDF) and a conductive agent (acetylene black + carbon nanotubes), the binder accounts for 85% of the functional coating, and the conductive agent accounts for 15%.

[0063] The active material coating 3 includes the active material LiCoO2, the conductive agent (acetylene black + carbon nanotubes) and the binder polyvinylidene fluoride (PVDF) in a weight ratio of 97.9:0.6:0.5.

[0064] negative electrode:

[0065] The negative electrode sheet includes a negative electrode current collector and a negative electrode active coating coated on the surface of the negative electrode current collector. The weight ratio of the negative electrode active material graphite, the dispersant sodium carboxymethyl cellulose, and the binder polyvinylidene fluoride is 97.7:1:1.3.

[0066] Isolation film:

[0067] The isolation membrane is made of polypropylene / polyethylene / polypropylene composite film.

[0068] Electrolyte:

[0069] Ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC) and propyl propionate (PP) are mixed in a volume ratio of 1:1:4:4, and then fully dried lithium salt LiPF6 is dissolved in a mixed organic solvent at a ratio of 1 mol / L to prepare an electrolyte.

[0070] Lithium-ion battery:

[0071] The positive electrode sheet, separator, and negative electrode sheet are wound or stacked to produce a bare cell, which is then packaged and injected with electrolyte to produce a finished lithium-ion battery.

[0072] Example 2

[0073] The lithium ion battery of Example 2 refers to Example 1, except that the resistance and thickness of the functional coating in the positive electrode are different. In this example, R is 2Ω, and the thickness of the functional coating 2 is 4 um.

[0074] Example 3

[0075] The lithium ion battery of Example 3 refers to Example 1, except that the specific surface area of ​​the functional coating in the positive electrode is different. In this embodiment, S is 0.13 m 2 / g.

[0076] Example 4

[0077] The lithium ion battery of Example 4 refers to Example 2, except that the specific surface area of ​​the functional coating in the positive electrode is different. In this embodiment, S is 0.13m 2 / g.

[0078] Example 5

[0079] The lithium ion battery of Example 5 refers to Example 2, except that the specific surface area of ​​the positive electrode active material is different. In this embodiment, S is 0.17 m 2 / g.

[0080] Example 6

[0081] The lithium ion battery of Example 6 refers to Example 2, except that the specific surface area of ​​the positive electrode active material and the thickness of the functional coating are different. In this embodiment, S is 0.19 m 2 / g, and the thickness of the functional coating 2 is 4.5 um.

[0082] Example 7

[0083] The lithium ion battery of Example 7 refers to Example 1, except that the width of the positive electrode active material, the resistance and the thickness of the functional coating are different. In this embodiment, L is 0.004m, R is 1.5Ω, and the thickness of the functional coating 2 is 2.5um.

[0084] Example 8

[0085] The lithium ion battery of Example 8 refers to Example 1, except that the width of the positive electrode active material is different. In this example, L is 0.006 m.

[0086] Comparative Example 1

[0087] The lithium ion battery of Comparative Example 1 refers to Example 1, except that the current collector of this comparative example is not coated with a functional coating but only with an active material coating.

[0088] Comparative Example 2

[0089] The lithium ion battery of Comparative Example 2 refers to Example 1, except that the specific surface area of ​​the positive electrode active material is different. In this comparative example, S is 0.21 m 2 / g.

[0090] Comparative Example 3

[0091] The lithium ion battery of Comparative Example 3 refers to Example 1, except that the width of the functional coating in the positive electrode is different, and L in this comparative example is 0.012 m.

[0092] Comparative Example 4

[0093] The lithium ion battery of Comparative Example 4 refers to Example 1, except that the resistance and thickness of the functional coating in the positive electrode are different. In this comparative example, R is 5Ω, and the thickness of the functional coating 2 is 6um.

[0094] Comparative Example 5

[0095] The lithium ion battery of comparative example 5 refers to embodiment 1, except that the resistance in the positive electrode and the thickness of the functional coating are different. In this comparative example, R is 0.5Ω and the thickness of the functional coating 2 is 1 um.

[0096] Comparative Example 6

[0097] The lithium ion battery of Comparative Example 6 refers to Example 1, except that the resistance and thickness of the functional coating in the positive electrode are different. In this comparative example, R is 4Ω, and the thickness of the functional coating 2 is 8um.

[0098] Comparative Example 7

[0099] The lithium ion battery of Comparative Example 7 refers to Example 1, except that the specific surface area of ​​the functional coating in the positive electrode is different. In this comparative example, S is 0.17 m 2 / g.

[0100] Resistance test method: The two-probe method is used to test the surface resistance of the positive and negative electrodes. When testing with the two-probe method, the terminals are placed at both ends of the sample, and the current at both ends of the sample is collected by inputting an AC voltage signal to obtain the sample resistance.

[0101] Performance test: At room temperature, first 2.8C to 4.5V, CV to 0.02C, 20 cycles. If the cell does not precipitate lithium, continue to increase the 0.1C test until the cell precipitates lithium, which is used as the charging capacity of the cell. CC means constant current charging, and CV means constant voltage charging.

[0102] The lithium electronic batteries obtained in the above Examples 1-8 and Comparative Examples 1-7 were subjected to a charge rate test, and the test results are shown in Table 1 below.

[0103] Table 1

[0104]

[0105]

[0106]

[0107] From the comparison of the results in Table 1 above, it can be seen that compared with the electrode sheets in Comparative Examples 1 to 7, the electrode sheets provided by the present application have a significantly improved charge rate. 2 / g, the charge rate is reduced, so the specific surface area S of the active material should be controlled at 0.1-0.2m 2 / g range, the surface density can be improved to a certain extent, thereby improving the charge rate. When the thickness of the functional coating and the thickness of the current collector are greater than the set range, the charge rate decreases, among which Example 2 is the best example.

[0108] In summary, the present application controls the ratio of the thickness of the functional coating to the thickness of the current collector to be 0.2-1, and the width L of the functional coating, the resistance R of the functional coating, and the specific surface area S of the active material of the active material coating satisfy the relationship: L·R / S>0.03, which can maintain a balance between the conductivity of the coating and the ability of the active material to detach. When lithium ions are released faster and the specific surface area is larger, the resistance of the coating is controlled to reduce the rate of detachment of the active material, and the rate at which the negative electrode receives lithium ions is reduced, so that a higher charge rate can be tolerated. It effectively improves the problem of reduced energy density of the battery cell due to control of lithium deposition in the battery.

[0109] According to the disclosure and teaching of the above description, the technicians in the field of the utility model can also change and modify the above implementation. Therefore, the utility model is not limited to the above specific implementation, and any obvious improvement, replacement or modification made by the technicians in this field on the basis of the utility model belongs to the protection scope of the utility model. In addition, although some specific terms are used in this specification, these terms are only for the convenience of explanation and do not constitute any limitation to the utility model.

Claims

1. An electrode sheet, characterized in that: include: current collector; A functional coating, coated on the edges of both sides of the current collector; An active material coating, coated on at least one surface of the current collector and covering the functional coating; The thickness ratio of the functional coating layer to the current collector is 0.2-1, and the resistance of the functional coating layer is greater than the resistance of the active material coating layer.

2. The electrode sheet according to claim 1, characterized in that: The parameters of the functional coating and the active material coating satisfy the relationship: L·R / S>0.03; Wherein, L is the width of the functional coating, R is the resistance of the functional coating, and S is the specific surface area of ​​the active material of the active material coating.

3. The electrode sheet according to claim 1, characterized in that: The width L of the functional coating is 0.002-0.01 m.

4. The electrode sheet according to claim 1, characterized in that: The resistance R of the functional coating is 0.1-4Ω.

5. The electrode sheet according to claim 1, characterized in that: The thickness of the functional coating is 1-10 um, and the thickness of the current collector is 4-8 um.

6. The electrode sheet according to claim 1, characterized in that: The specific surface area S of the active material in the active material coating is 0.1 to 0.2 m 2 / g.

7. The electrode sheet according to claim 1, characterized in that: The active material coating has a resistance of 0.1 to 2Ω.

8. The electrode sheet according to claim 1, characterized in that: The active material coating comprises: A first active material coating layer, coated on at least one surface of the current collector; The second active material coating is connected to both side edges of the first active material coating and covers the functional coating.

9. The electrode sheet according to claim 8, characterized in that: The thickness ratio of the second active material coating layer to the functional coating layer is 3-10.

10. The electrode sheet according to claim 8, characterized in that: The thickness of the first active material coating is 30-50 um.

11. The electrode sheet according to claim 8, characterized in that: The thickness of the second active material coating is 20-49 um.

12. A lithium ion battery, characterized in that: The electrode sheet comprises the electrode sheet according to any one of claims 1 to 11.

Citation Information

Cited By

  • Positive pole piece and battery

    CN121565786A

  • Positive electrode sheet and battery

    CN121565786B